Mediastinal Parathyroid Adenoma with Osteitis Fibrosis Cystica: Robot-Assisted Thoracic Surgical Resection. Issue 6 (November 2014) - Sridhar, Praveen; Steenkamp, Devin W.; Lee, Stephanie L.; Ebright, Michael I.; Litle, Virginia R.; Fernando, Hiran C.
Mediastinal parathyroid adenomas can be resected by sternotomy or video-assisted thoracoscopic surgery. Robot-assisted thoracic surgical approaches have recently been described. We report robotassisted thoracic surgical resection of a mediastinal parathyroid in a morbidly obese patient. Additional comorbidities included multiple pathological fractures related to hypercalcemia. Intraoperative parathyroid hormone levels confirmed successful removal of the adenoma. Hungry bone syndrome developed after surgery but eventually resolved. Robotassisted thoracic surgery avoided the need for sternotomy and associated concerns related to poor bone healing. Robot-assisted thoracic surgery has potential advantages over video-assisted thoracoscopic surgery in patients with obesity because of easier instrument articulation within the thoracic cavity rather than at the chest wall.